Understanding contemporary governmentality: Death, healing and colonial patriarchy in Canada - Leichnitz, Jordan (University of Ottawa (Canada), 2009)
This thesis explores the changing shape of colonial governmentality in Canada through an examination of the complex relationship between the representation and treatment of Indigenous women in Canada and power relations underlying the creation of "healing prisons" run for Indigenous women offenders. It is hypothesized that there is a mutually constitutive connection between the discursive and literal space of death faced by Indigenous women in Canada, and the deployment of specialized prisons as a gendered and raced political technology of the colonial state. Drawing on a wide range of theoretical perspectives to search for the reciprocal links between these disparate phenomena, this paper analyses dominant discourses to understand the emergence of new responsibilizing forms of colonial governance with particularly gendered effects. It concludes with an examination of the possibilities for utilizing a similar de-colonizing critique to counter emerging forms of colonial governance in the contemporary neo-liberal state.
Keywords: Political Science, General.